A PRELIMINARY STUDY OF INVESTIGATING OF COMPOUND GROUP CONTAINED IN ETHANOLIC EXTRACT OF MAHAGONY (Swietenia mahagoni L. Jacq.) SEEDS RELATED TO Α-GLUCOSIDASE INHIBITION - Anjar Purba Asmara (Jurnal Natural, 2018)
A preliminary study to determine the group of compound contained in the ethanolic extract of mahagony (Swietenia mahagoni L. Jacq.) seeds and its inhibitory activity to a-glucosidase enzyme has been done. The information from this study will be used in the further investigation about the specific constituents related to the bioactivity. The seed was grounded and then extracted with ethanol by maceration technique. The crude extract was separated with liquid-liquid extraction by using n-hexane, ethyl acetate, and methanol as the solvents. The best eluent for isolation, chloroform:ethanol (1:1), was determined by thin layer chromatography while alumina as stationary phase. The isolation step with column chromatography gave two types of isolates, yellow and colorless isolate. In order to get information about the compound, the crude extract was subjected to phytochemical assignment and the isolate with the better activity was analyzed by infrared spectroscopy. The inhibitory activity for the yellow isolate with IC50 as 19.345 ppm was better than the colorless isolate. Therefore, the IR spectroscopy assay was subjected to the yellow isolate. Based on the comparison IR spectra with literatures, it has suggested that the yellow isolate contains tetranortriterpenoid or limonoid group.